Tracing the links between executive compensation structure and firm performance: evidence from the Brazilian market. Issue 7 (23rd October 2020) - Dias, Alexandre; Vieira, Victor; Figlioli, Bruno
Abstract : Purpose: This study aims to investigate how different executive compensation structures were related to the performance of firms. Design/methodology/approach: This study was based on a sample of companies with the highest standards of corporate governance listed on the Brazilian Stock Exchange. We adopted the multiple correspondence analysis followed by the hierarchical cluster analysis to propose a typology defined by fixed and variable components of the executive compensation and multiple firm performance indicators. Findings: The analysis produced three clusters, which were submitted to robustness tests, highlighting that companies used the compensatory incentives in striking distinct ways as governance mechanisms. The study found a positive relationship between the performance of companies and the variable incentives of executive compensation, especially the long-term incentive, as well as a negative relationship between the performance of firms and the fixed component of the compensation structure. Research limitations/implications: This research, whose sample was based on an emerging market, adds empirical evidence to the literature. However, future studies are invited to address the relationships between executive compensation structures and firm performance in other markets, as well as to examine these relationships in companies with distinct levels of governance. Practical implications: This study provides insights on how the incentive structure can be adopted as an efficient governance mechanism, especially for companies in emerging markets. Originality/value: The main novelty of this paper is that the methodological strategy used here enabled the authors to discriminate distinct executive compensation structures and establish a relationship between these compensation structures and different types of performance indicators.